A field life prediction model of electronic modules corroded by S8 gas released from rubber ducts in-vehicle engine rooms. (19th May 2018) - Abe, Hiroyuki; Yasukawa, Akio; Minamitani, Rintaro; Saito, Hiroyuki
ABSTRACT: A model which predict the field life of electronic modules corroded by S8 gas in vehicle engine rooms is constructed. The in-vehicle module field life is predicted from the accelerated test results of module alone and the measured results of in-vehicle module field environment conditions. In the modules, a circuit substrate with Ag wiring is placed on a baseplate within a housing and sealed with silicone. The S8 gas is produced by the release of the free sulphur of rubber ducts in engine room at the maximum temperature holding time after engine stop. This S8 gas permeates the silicone seal and corrodes the Ag wiring. The ratio of the corroded part thickness to the initial thickness of the Ag wiring increases with the increase of the number of engine start/stop cycles. The calculated results coincide well with the observed results of the corrosion thickness in an actual vehicle.